RAPD-DNA analysis of yeast isolated from Kazakh national fermented milk drinks (Experimental biology, 2019)
RAPD-analysis of DNA of microorganisms-producers of Kazakh national milk beverages, kumiss and shoubat, had allowed to specify the systematic position of some previously undefined laboratory cultures of yeasts.